Investigating the High-Temperature (100 °C - 200 °C) Dissolution and Sulfidation of As₂O₃ Stored at the Giant Mine, NWT, Canada - Tennant, Evelyn (Université d'Ottawa / University of Ottawa, 2023)
The Giant Mine near Yellowknife, NWT generated 237 000 tonnes of arsenic-trioxide (As₂O₃)-rich dust as a by-product of gold mining during its years of operation (1948 - 2004). Arsenic trioxide is a relatively soluble form of arsenic (As) and is currently stored in the mine, posing a threat of contamination to the adjacent Great Slave Lake. This research investigates the potential for permanent remediation of the As₂O₃ using sulfidation to transform it to arsenic trisulfide (As₂S₃). Knowing that aqueous As₂O₃ readily reacts with sulfide (Ostermeyer, 2021), it was determined that the most practical and effective method to achieve sulfidation of the Giant Mine dust is to first dissolve the As₂O₃ and then conduct the reaction with sulfide. The optimal conditions at which to dissolve As₂O₃ were investigated. The solubility and dissolution rate in water were shown to increase with temperature, with solubility increasing from 185.7 g As₂O₃/kg water at 140 °C to 250.6 g As₂O₃/kg water at 180 °C. Qualitative demonstrations of the rate of dissolution show that ≥ 90 % of the As₂O₃ dissolved within 5 minutes at 140 °C, and 4 minutes at 180 °C; previous research indicates that time to equilibrium is > 24 hours at 60 °C (CANMET, 2000). Reaction of Giant-Mine material in water at elevated temperatures (140 °C - 200 °C) for 10 to 30 minutes consistently resulted in dissolution of approximately 80 wt. % of the initial solid-phase As concentrations, representing almost all the As₂O₃, yielding undissolved residues (≈ 40 wt. % of initial mass). The persistence of As in these residues is likely due to it being hosted in As₂O₃ - Sb₂O₃ solid solutions and low-solubility Fe-oxide phases in the initial sample (CANMET, 2000; Poirier, 2004).